Sociologia dos Leitores Sociologia da Leitura ou os Homens Leem A Bola que Leem os Homens ao Lerem A Bola? - Freitas, Eduardo (1994)
Sociologia dos Leitores Sociologia da Leitura ou os Homens Leem A Bola que Leem os Homens ao Lerem A Bola?